Nuclear Technology and Public Health - Essien, I.O. (SCHOOL SCIENCE, 2013)
The words “nuclear technology” registers in many people’s mind an atomic and a nuclear bomb hence nothing more than destruction. This impression is not always correct since nuclear technology is also used for peaceful purposes. Isotopes of some elements emit radiation as their nuclear decay and they are called radioactive isotopes, radioisotopes or radionuclides. Some of these radionuclides occur naturally while others are artificial and the study of these radionuclides is called nuclear science. Nuclear technology is therefore the various nuclear techniques developed from nuclear science which make use of mainly radioisotopes or radiation procedures in response to the challenges imposed by the nuclear age. Their range of application is extremely broad which may be both constructive and destructive. The application of these nuclear techniques will therefore have some advantages and disadvantages on public health; since these radionuclides will be used in the environment. The inhabitants of the environment such as man, animals and plants may benefit from the detrimental effects of the nuclear accidents and radiations.